PERAN MEDIASI EMPLOYEE ENGAGEMENT PADA FAKTOR-FAKTOR YANG MEMPENGARUHI TURNOVER INTENTION - Reski Putri Amelia; Hendra Lukito (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
This research was conducted aiming to find out the factors that influence turnover intention by mediating employee engagement at Bank Nagari employees of Padang City Center in 2016-2019. Independent variables in this research are organizational justice and employer branding, turnover intention is used as dependent variable, and employee engagement is used as a mediating variable. The technique of determining the number of samples is the Isaac & Michael table with level of 10% so that 133 employees are obtained as samples in this research. Data analysis techniques used descriptive analysis using SPSS and validity and reliability testing using SmartPLS. Where the results obtained are organizational justice and employer branding has a significant and negative effect on turnover intention and there is an indirect effect of employee engagement. Keywords: Organizational Justice, Employer Branding, Employee Engagement, Turnover Intention